Effects of feed solution pH and draw solution concentration on the performance of phenolic compounds removal in forward osmosis process. Issue 3 (June 2017) - Zhang, Xiaohui; Li, Quangeng; Wang, Jun; Li, Jie; Zhao, Changwei; Hou, Deyin
Highlights: Typical phenolic compounds in the coal gasification wastewater were separated by FO. Steric hindrance played a major role on the rejection of the phenolic compounds. Higher draw solution concentration resulted in high rejection of phenolic compounds. A semi-empirical model of good fit was validated with the experimental data. Abstract: The toxic phenolic compounds presented in the coal gasification wastewater are required to be removed to meet the stringent wastewater discharge regulation. Utilizing forward osmosis (FO) in this process can not only remove these toxic contaminants but also reclaim the water resources. In this study, the feasibility of using FO process to treat coal gasification wastewater was demonstrated using a commercial polyamide thin-film composite membrane. The effects of main operating conditions (i.e. feed solution pH and draw solution NaCl concentration) on the phenolic compound removal were systemically evaluated. Three typical small molecular phenolic compounds (phenol, resorcinol, and 4-propylphenol) in coal gasification wastewater were used for the study on the performance of phenolic compounds removal using FO process. The results indicated that, due to the change of surface charge of the phenolic compounds and the FO membrane surface under different pH conditions, these phenolic compounds were better removed at alkaline conditions. In addition, it was found that increasing the draw solution NaCl concentration encouraged the water permeation flux because of the enhanced osmotic pressure; as a result, the rejection of phenolic compounds was improved. Furthermore, a semi-empirical model based on the solution-diffusion mechanism was proposed in this study to predict the water permeation and phenolic compound fluxes under different feed solution pH values and draw solution NaCl concentrations, good fit between the experimental and simulation results were found which validated the proposed model.